2020
DOI: 10.1088/1742-6596/1525/1/012102
|View full text |Cite
|
Sign up to set email alerts
|

A 3D track finder for the Belle II CDC L1 trigger

Abstract: Machine learning methods are integrated into the pipelined first level (L1) track trigger of the upgraded flavor physics experiment Belle II at KEK in Tsukuba, Japan. The novel triggering techniques cope with the severe background from events outside the small collision region provided by the new SuperKEKB asymmetric-energy electron-positron collider. Using the precise drift-time information of the central drift chamber which provides axial and stereo wire layers, a neural network L1 trigger estimates the 3D t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This will be done by a 3D Hough transformation for further efficiency increases. It has already been shown in simulation that a more accurate resolution and larger solid angle coverage can be achieved (Skambraks et al, 2020 ).…”
Section: Exemplars Of Domain Applicationsmentioning
confidence: 95%
“…This will be done by a 3D Hough transformation for further efficiency increases. It has already been shown in simulation that a more accurate resolution and larger solid angle coverage can be achieved (Skambraks et al, 2020 ).…”
Section: Exemplars Of Domain Applicationsmentioning
confidence: 95%
“…Currently, the z-Vertex Track Trigger requires a found 2-dimensional track from the 2D Finder. It has been shown that a 3D Hough [2] preprocessing gives better results than the 2D finder, especially in the regions of shallow polar scattering angles and low transverse momentua. Prototype designs already exist which are also implemented in FPGA.…”
Section: Future Updates 3d Houghmentioning
confidence: 99%
“…The resolution of the constructed transverse momentum and azimuthal angle was tested with 150 thousand single-electron events with 𝑝 𝑡 ranging from 160 MeV/c to 1500 MeV/c. According to The CDC detector at Belle II experiment [18] has a similar detector architecture to the MDC detector at STCF. Therefore, the results of 2D track reconstruction for the CDC L1 trigger can be used as a reference.…”
Section: Performance Of Parameter Estimationmentioning
confidence: 99%
“…Even though the FPGA logic uses quadratic interpolation and fixed-point numbers, the precision of azimuthal angle reconstruction is almost the same as the software when 𝑝 𝑡 is above 180 MeV. When 𝑝 𝑡 is close to 160 MeV, the interpolated value error becomes large due to the large derivative of the function in equation 3.4.The CDC detector at Belle II experiment[18] has a similar detector architecture to the MDC detector at STCF. Therefore, the results of 2D track reconstruction for the CDC L1 trigger can be used as a reference.…”
mentioning
confidence: 99%